2018
DOI: 10.1177/1538192717751205
|View full text |Cite
|
Sign up to set email alerts
|

“Es como una Familia”: Bridging Emotional Support With Academic and Professional Development Through the Acquisition of Capital in Latinx Student Organizations

Abstract: This study explored the ways Latinx-based organizations assist students in navigating college and career preparation. Data consist of in-depth interviews with 17 first-generation Latinx students attending two predominantly White institutions in the Midwest. I employed Bourdieu’s social reproduction theory to examine the ways Latinx student organizations cultivate social and cultural capital among participants. Findings reveal that peers in Latinx-based organizations share capital relevant to navigating college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Other research has also documented benefits of ethnic-based organizations for Latina/o/xs (Luedke, 2018; González, 2002; Villalpando, 2003). Luedke (2018) examined ways Latinx student organizations influenced students’ collegiate experiences and found that the organizations provided a sense of familia (family) and served as a source of capital that helped them to successfully navigate their academic experience.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has also documented benefits of ethnic-based organizations for Latina/o/xs (Luedke, 2018; González, 2002; Villalpando, 2003). Luedke (2018) examined ways Latinx student organizations influenced students’ collegiate experiences and found that the organizations provided a sense of familia (family) and served as a source of capital that helped them to successfully navigate their academic experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ethnic-based student organizations are a particular campus subculture and form of collective cultural agent that have been examined in the literature and can play an important role in the experiences of Latina/o/x college students (González, 2002; Kim, Park, & Koo, 2015; Luedke, 2018; Museus, 2008b; Villalpando, 2003). Ethnic student organizations may take the form of “fraternities and sororities open solely to membership among one racial/ethnic group, cultural groups that celebrate one specific racial or ethnic heritage, and activist organizations that concentrate on political interests for a certain race or ethnicity” (Inkelas, 2004, p. 285).…”
mentioning
confidence: 99%
“…While students’ ideas about race may be under examined within the community college context, there is evidence that their conceptions of race matter tremendously in terms of how they engage in the college environment. Namely, students’ ideas about race matter because, like other diversity‐related perceptions, they influence individual attitudes and behaviors that can inform how they interact and engage on campus (Bowman & Park, ; Garcia, ; Luedke, ). More specifically, when students think about race in more narrow biological ways, they tend to harbor more negative racial stereotypes of other students (Shih, Bonam, Sanchez, & Peck, ) and be less prone to engage with diverse friend groups (Williams & Eberhardt, , as cited in Johnston‐Guerrero, ).…”
Section: Why Racial Conceptualization Mattersmentioning
confidence: 99%
“…Student organization involvement can provide support networks and cultural capital to minoritized students, particularly those attending predominantly White institutions. Several studies have demonstrated how Latinx-based organizations can provide support and family-like environments for Latinx students [7], [8], [43], [86]. Luedke [86] described how students gained social capital through their involvement that supported their career planning and networking with employers.…”
Section: Rq3mentioning
confidence: 99%
“…Several studies have demonstrated how Latinx-based organizations can provide support and family-like environments for Latinx students [7], [8], [43], [86]. Luedke [86] described how students gained social capital through their involvement that supported their career planning and networking with employers. Banda and Flowers III [8] noted that most of their participants described the support and sense of belonging they received through involvement in identity-based student organizations.…”
Section: Rq3mentioning
confidence: 99%